Pengaruh penggantian sebahagian pasir dengan debu kuari ke atas ciri konkrit prestasi tinggi baru - Muhammad Fauzi Mohd.Zain,; Sudharshan Naidu Raman,; Md. Safiuddin, (2000)
This study discusses the influence of partial replacement of sand with quarry dust on the properties of fresh high performance concrete. Considering the decrease in the sources of natural sand, it is necessary to identify alternative source, such as quarry dust to reduce the utilisation of sand in the industries, which requires it. In this study,replacement proportion of sand with quarry dust that was practised was 20% in all the high performance concrete mixes except in the normal Portland cement control high performance concrete mix. The properties of fresh high performance concrete were determined in the aspects of slump, slump flow, V-Funnel flow, air content,density and temperature. Results obtained showed that partial replacement of sand with quarry dust was able to increase the workability and flowability, and also the air content of fresh high performance concrete. Besides that, it was observed that V-Funnel flow was more suitable to determine the flowability of fresh high performance concrete compared to the conventional slump flow